2017
DOI: 10.14814/phy2.13066
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide potentiates the afferent drive to prefrontal cortex in vivo

Abstract: The knowledge on real‐time neurophysiological effects of acetazolamide is still far behind the wide clinical use of this drug. Acetazolamide – a carbonic anhydrase inhibitor – has been shown to affect the neuromuscular transmission, implying a pH‐mediated influence on the central synaptic transmission. To start filling such a gap, we chose a central substrate: hippocampal‐prefrontal cortical projections; and a synaptic phenomenon: paired‐pulse facilitation (a form of synaptic plasticity) to probe this drug's e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…The mechanisms underpinning CAs actions on cognition remain largely unidentified. Modulation of CAs activity alters the buffering capacity, thus influencing intracellular and extracellular pH value, therefore affecting protein NMDA and GABA receptors function [58]. Early studies demonstrated that the associated activation of multi-synaptic inputs on pyramidal neurons in the hippocampal CA1 region transiently transform GABAergic IPSPs to EPSPs; this transformation depends on CA activation as it busts HCO 3 − intracellular concentrations favouring its efflux through the GABA A receptor channel [39,59].…”
Section: The Role Of Carbonic Anhydrases In Cognitionmentioning
confidence: 99%
“…The mechanisms underpinning CAs actions on cognition remain largely unidentified. Modulation of CAs activity alters the buffering capacity, thus influencing intracellular and extracellular pH value, therefore affecting protein NMDA and GABA receptors function [58]. Early studies demonstrated that the associated activation of multi-synaptic inputs on pyramidal neurons in the hippocampal CA1 region transiently transform GABAergic IPSPs to EPSPs; this transformation depends on CA activation as it busts HCO 3 − intracellular concentrations favouring its efflux through the GABA A receptor channel [39,59].…”
Section: The Role Of Carbonic Anhydrases In Cognitionmentioning
confidence: 99%
“…In particular, brief stimulation of the infralimbic cortex (a subregion of the vmPFC) was found to reduce fear memory and strengthened extinction (12,49). More recently, systemic administration of ACTZ was found to inhibit prefrontal cortical single-unit firing in vivo, leading to reduced basal neuronal activity of the prefrontal cortex (50). Taken together, these findings suggest that ACTZ impairs fear extinction memory through inhibition of vmPFC firing.…”
Section: Discussionmentioning
confidence: 92%
“…CA is present in many tissues of the body, including the brain, where catalyzes a reversible reaction between CO 2 hydration and HCO 2 3 dehydration. However, the mechanisms of how this therapeutic effect is achieved are not known (Bueno-Junior et al, 2017;Ruusuvuori and Kaila, 2014). Zhang et al (2010) used the pH-sensitive fluorescence of Yellow Fluorescent Protein transgenically expressed in mouse motor nerve terminals to report pH changes due to presynaptic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…CA is present in many tissues of the body, including the brain, where catalyzes a reversible reaction between CO 2 hydration and HCO3 dehydration. However, the mechanisms of how this therapeutic effect is achieved are not known (Bueno‐Junior et al, ; Ruusuvuori and Kaila, ).…”
Section: Discussionmentioning
confidence: 99%